Functional Polymorphisms of the Arachidonic Acid Pathway Associate with Risks and Clinical Outcomes of Allergic Diseases - Sio, Yang Yie; Shi, Ping; Matta, Sri Anusha; Fok, Rachel Yu Ting; Chiang, Wen Chin; Say, Yee How*; Chew, Fook Tim (Karger Publishers, 2023)
Introduction: The arachidonic acid (AA) pathway plays a crucial role in allergic inflammatory diseases; however, the functional roles of allergy-associated single nucleotide polymorphisms (SNPs) in this pathway remain incompletely illustrated.